A black-hole mass measurement from molecular gas kinematics in NGC4526 - Davis, T; Bureau, M; Cappellari, M; Sarzi, M; Blitz, L (2013)
The masses of the supermassive black holes found in galaxy bulges are correlated with a multitude of galaxy properties, leading to suggestions that galaxies and black holes may evolve together. The number of reliably measured black-hole masses is small, and the number of methods for measuring them is limited, holding back attempts to understand this co-evolution. Directly measuring black-hole masses is currently possible with stellar kinematics (in early-type galaxies), ionized-gas kinematics (in some spiral and early-type galaxies) and in rare objects that have central maser emission. Here we report that by modelling the effect of a black hole on the kinematics of molecular gas it is possible to fit interferometric observations of CO emission and thereby accurately estimate black-hole masses. We study the dynamics of the gas in the early-type galaxy NGC 4526, and obtain a best fit that requires the presence of a central dark object of× 10 8 solar masses (3σ confidence limit). With the next-generation millimetre-wavelength interferometers these observations could be reproduced in galaxies out to 75 megaparsecs in less than 5 hours of observing time. The use of molecular gas as a kinematic tracer should thus allow one to estimate black-hole masses in hundreds of galaxies in the local Universe, many more than are accessible with current techniques. © 2013 Macmillan Publishers Limited. All rights reserved.